Prenatal and Early-Life Exposure to Parabens: Sources, Reduction Strategies, and Developmental Health Effects - A literature review - Olejnik-Chlewicka, Klaudia; Puchalski, Konrad; Liszka, Paweł; Perediatkiewicz, Jakub; Zasiadła, Marta; Patrzykąt, Klaudia Martyna; Urbański, Wojciech; Łuczak, Paweł Mateusz; Brodowski, Jakub; Ogórek, Agata (Quality in Sport, 2026)
Informations and purpose: Parabens are widely used preservatives found in cosmetics, pharmaceuticals, foods and household products. Increasing evidence shows that women of reproductive age, including pregnant women, are consistently exposed to these endocrine-disrupting chemicals, which may influence fetal and early-life development. Understanding exposure levels and potential health consequences is important for both public health and clinical practice. Methods: A systematic literature search was performed to identify studies evaluating paraben exposure during pregnancy and its effects on fetal and early childhood health. The literature search included studies published from 2019-2024 and contained searches of PubMed, Scopus, Science Direct and open access databases. Results: Parabens are widely detected in maternal and fetal matrices. Exposure to parabens in utero has been shown to result in changes to fetal size, metabolic and hormone-related factors and an increased risk of developing atopic and respiratory diseases in early childhood.Reported mechanisms involve endocrine disruption(specifically acting like estrogens and anti-androgens), oxidative stress, immune modulation and possible epigenetic effects. Conclusion: Current evidence indicates that parabens may influence child development through several biological pathways, with effects observable from fetal life into early childhood. Although causality remains to be fully established, reducing paraben exposure in pregnancy and early life—particularly from cosmetic and dermal sources—appears advisable. Public health measures promoting informed consumer choices may further mitigate exposure.